2000
DOI: 10.1080/00288233.2000.9513448
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental factors affecting lamb survival at birth and through to weaning

Abstract: Pedigree and early performance records from lambs on three New Zealand research stations, involving 51 station-years of data (55 146 recorded lambs born), were analysed in order to study genetic and environmental factors affecting perinatal and preweaning survival. Mean birth weights at each site were very similar, being 4.26 kg at Woodlands, 4.22 kg at Tokanui, and 4.32 kg at Rotomahana Station. Total survival rates to weaning (preweaning survival) across sites averaged 79.0, 78.9, and 80.1%, respectively. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
69
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 8 publications
16
69
2
Order By: Relevance
“…sex) for lambs that died at birth, which tended to bias the data. However, for the lambs that died at birth and had sex recorded the ratio of males to females was 1 : 2, which follows published literature (Dalton et al, 1980;Morris et al, 2000). This is probably mostly due to its effect on birth weight (Nash et al, 1996;Holst et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…sex) for lambs that died at birth, which tended to bias the data. However, for the lambs that died at birth and had sex recorded the ratio of males to females was 1 : 2, which follows published literature (Dalton et al, 1980;Morris et al, 2000). This is probably mostly due to its effect on birth weight (Nash et al, 1996;Holst et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…This is probably mostly due to its effect on birth weight (Nash et al, 1996;Holst et al, 2002). The effect of age of ewe on lamb mortality has been shown by many authors to be important; often reported to generally decline with age up to the fourth or fifth parities (Dalton et al, 1980;Morris et al, 2000;Sawalha et al, 2007). In this study, the opposite was found.…”
Section: Discussioncontrasting
confidence: 51%
“…Single born lambs had higher mortality rate at birth but lower hazard rate afterwards (from 1 to 14 days). Morris et al (2000) found generally similar effects, with a higher rate of mortality at birth for lambs born to 2-year-old dams and a lower preweaning survival for lambs born to 2-and 5-year-old dams. Therefore, to reduce Lamb survival in Scottish Blackface sheep early postnatal lamb mortality, particular attention should be paid to 2-and 6-year-old ewes and their lambs and to twinand triplet-born lambs.…”
Section: Discussionmentioning
confidence: 63%
“…Early lamb survival is a complex trait that is influenced by the ewe's maternal ability and the lamb's capability for survival, in addition to the management practices and environmental variables at the time of birth and during the rearing period (Morris et al, 2000;Southey et al, 2001). Most studies of lamb survival (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation